Likit biyopside glioblastoma multiforme genetik biyobelirteçlerinin araştırılması / Research on glioblastoma multiforme genetic biomarkers in liquid biopsy - KAYA, BÜŞRA (My University, 2023)
Glioblastoma multiforme hastalarının likit biyopsi örneklerinde genetik biyobelirteçlerin yakalanması ve keşfi
Capture and discovery of genetic biomarkers in liquid biopsy samples of glioblastoma multiforme patients